Management of human service programs. - Lewis, Judith A., 1939-; Packard, Thomas Roy.; Lewis, Michael D., 1937- (Belmont, CA : Thomson Brooks/Cole, 2012)
This book takes the reader along the road toward understanding the purposes and processes of human service management. [In the book, the authors] begin by addressing some of the management challenges that may be unique to human service settings. [They] examine the environments that have an impact on human service organization and then move on to explore program planning, organizational design, human resource management, supervision, finances, information systems, program evaluation, leadership, and organizational change. -Pref.
Facing the challenges of management -- Knowing the environment -- Planning and program design -- Applying organizational theories -- Creating organizational designs -- Developing and managing human resources -- Building supervisory relationships -- Managing finances to meet program goals -- Designing and using information systems -- Evaluating human service programs -- Leading and changing human service organizations -- Achieving and maintaining organizational excellence -- Appendix: Management audit.
Rev. ed. of: Management of human service programs / Judith A. Lewis ... [et al.]. 2nd ed. c2001.
Includes bibliographical references and indexes.
Keywords: Human Services -- Management; Human services -- United States -- Management -- Case studies; Services sociaux -- Administration; Services sociaux -- ats-Unis -- Administration -- Cas, udes de